PMK IMPLEMENTATION STRATEGY NUMBER 28 OF 2024 ON OPTIMIZING TAXATION AND CUSTOMS FACILITIES TO SUPPORT THE DEVELOPMENT OF THE ARCHIPELAGO'S CAPITAL CITY - Latasya, Elsa; Khasanah, Khasanah; Antasari, Dewi Wungkus (Accounting Studies and Tax Journal (COUNT), 2025)
This study discusses the implementation strategy of the Minister of Finance Regulation (PMK) Number 28 of 2024 in optimizing tax and customs facilities to support the development of the Nusantara Capital City (IKN). This policy aims to create a conducive investment climate by providing various fiscal incentives, such as income tax reductions, VAT exemptions and Luxury Sales Tax, as well as import duties. The research method used is qualitative descriptive with a phenomenological approach, which relies on primary data from interviews with tax consultants and construction commissioners as well as secondary data from literature studies. The results of the study show that although this policy has great potential in attracting investment and accelerating the development of IKN, there are a number of challenges and obstacles in its implementation. Some of the main obstacles include lack of socialization, administrative complexity, and regulatory barriers. The digitalization of the tax and customs administration system is identified as a strategic step in overcoming these barriers. Therefore, stricter supervision is needed in the field of fiscal administration and operations. The evaluation focused on the effectiveness of the realization of fiscal incentives in increasing investment and the compliance of facility recipients with applicable regulations. The Government of Indonesia is advised to strengthen bilateral relations with investor countries through investment protection agreements, harmonization of international tax standards, and more intensive technical and diplomatic cooperation to build trust and increase foreign capital flows that support the development of the IKN.